Neuroacanthocytosis Syndromes II - Walker, Ruth H.; Saiki, Shinji; Danek, Adrian; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
Neuroacanthocytosis refers to a group of rare neurodegenerative disorders, the symptoms of which typically resemble Huntington’s disease. One defining feature is the presence of thorny red blood cells (acanthocytes); however, neither the role of the genetic mutations in causing acanthocytosis, nor the connection with the basal ganglia neurodegeneration, is yet understood. At present there is no cure for these disorders and treatment is purely symptomatic. Awareness of neuroacanthocytosis disorders has increased significantly in recent years. There have been a number of important developments in the field since the publication of the first volume, Neuroacanthocytosis Syndromes. This book contains the latest research in this area. Recent advances have identified the range of mutations in the causative genes, shedding light on potential phenotypegenotype correlations. Studies of the proteins affected in these disorders have resulted in increased understanding of their functions and distribution. In vitro studies have identified potential protein interactions, which have important implications for pathophysiology. Work on erythrocyte membranes suggests mechanisms for the generation of acanthocytes. Animal models are being generated which will greatly facilitate understanding the role of gene mutations in humans, and provide the foundation for possible therapeutic interventions. In addition, advances in other neurodegenerative disorders, such as Huntington’s and Parkinson’s diseases, have implications for neuroacanthocytosis. .
The Neuroacanthocytosis Syndromes -- Neuroacanthocytosis Syndromes — A Current Overview -- Differential Diagnosis of Chorea -- An Update on the Hardie Neuroacanthocytosis Series -- Update on McLeod Syndrome -- Huntington’s Disease-Like 2 -- Neuroacanthocytosis in Japan — Review of the Literature and Cases -- Basic Research - Proteins and Erythrocytes -- The Function of Chorein -- Recent Studies of Kell and XK: Expression Profi les of Mouse Kell and XK mRNA -- Questions of Cell Shape -- Neuroacanthocytosis-Related Changes in Erythrocyte Membrane Organization and Function -- McLeod Syndrome: A Perspective from Japanese Blood Centers -- Animal Models -- A Mouse Model of Chorea-Acanthocytosis -- The Structural Basis of Brain Involvement in Neuroacanthocytosis -- Functional Imaging in Neuroacanthocytosis -- Volumetric Neuroimaging in Neuroacanthocytosis -- Neuropathology of Chorea-Acanthocytosis -- The Neuropathology of McLeod Syndrome -- Cerebral Involvement in McLeod Syndrome: The First Autopsy Revisited -- Clinical Aspects and Therapy -- Psychiatric Morbidity in Neuroacanthocytosis -- Muscular Aspects of Chorea-Acanthocytosis -- Autonomic Dysfunction in Neuroacanthocytosis and Causes of Sudden Death: Analysis of a Case of Chorea-Acanthocytosis with Dysautonomia -- Sleep Disorders in Neuroacanthocytosis -- Neurosurgery for Neuroacanthocytosis -- Multidisciplinary Neurorehabilitation in Chorea-Acanthocytosis: A Case Study -- The Way Forward -- “Virtual Neuroacanthocytosis Institute”: A Look Forward.
Keywords: Neurosciences; Neurology .; Human genetics; Neurosciences; Neurology; Human Genetics